Preparation of Research Staff in Distance Education in Mexico from an Interdisciplinary and Historical Perspective - Ramírez-Díaz, José Antonio (Revista Electrónica Educare, 2021)
This article was written with results obtained from the research titled CONACYT as a governing body of the state capacities in the relationship of science with the education sector (Ramírez Díaz, 2020a). The article analyzes the impact of the implementation of science policy on the formation of the disciplinary education field in Mexico. The theme reviewed in this paper relates the development of disciplines associated with education to institutionalization events of distance education; its objective is to deepen the complexity in the training process of distance education specialists to optimize it. The research method was based on historiography and interviews with postgraduates in education. The results allowed outlining theoretical limits to the formation of specialized academic communities, in which there is a bridge between social and economic demands at the macro level with regulatory processes and the academic culture of the formation groups. The theory of “Social Framework” was used to establish the relationship. The impossibility of placing results empirically and within a specific context that allows us to characterize how “Social Frameworks” operate in academic groups is recognized as limiting. The work produced theoretical information to conduct empirical research on specialized training and established generic fields of the constitution of specialized research communities.